1986
DOI: 10.1128/iai.51.3.919-926.1986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood group on the availability of receptors for attachment of uropathogenic Escherichia coli

Abstract: Escherichia coli strains with defined receptor specificity were used as probes to analyze the individual variation in host cell receptors with respect to blood groups. The adhesins were initially characterized as mannose sensitive (MS), mannose resistant (MR), or nonagglutinating (-). The receptor specificity of the strains with MR adhesins was defined by agglutination of synthetic Galkl-4Galp covalently linked via a spacer arm, (CH2)2S(CH2)2CO-H-bovine serum albumin (BSA) to BSA-latex beads as specific for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 26 publications
2
42
1
Order By: Relevance
“…A hypothesis has been suggested that the decreased susceptibility of secretors to peptic ulcer disease is due to the presence of terminal fucose resi-dues of H type 2 and Le being important receptors for H. pylori, and that the presence of these antigenic determinants in the mucosa of secretors, protects them from heavy colonisation by infecting organisms [12]. Previous reports have demonstrated that epithelial cells of non-secretors bind larger numbers of micro-organisms than cells of secretors, speci¢cally, uropathogenic strains of Escherichia coli [15], Candida albicans [16], and Staphylococcus aureus [9].…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis has been suggested that the decreased susceptibility of secretors to peptic ulcer disease is due to the presence of terminal fucose resi-dues of H type 2 and Le being important receptors for H. pylori, and that the presence of these antigenic determinants in the mucosa of secretors, protects them from heavy colonisation by infecting organisms [12]. Previous reports have demonstrated that epithelial cells of non-secretors bind larger numbers of micro-organisms than cells of secretors, speci¢cally, uropathogenic strains of Escherichia coli [15], Candida albicans [16], and Staphylococcus aureus [9].…”
Section: Discussionmentioning
confidence: 99%
“…Small numbers of microorganisms might elicit a modest inflammatory response and induce antibodies specific for the particular strain. Second, in the non-immune non-secretor, colonization might not be inhibited but enhanced by interactions with Lewis a antigens as suggested by studies with candida [22,23] and by increased attachment of uropathogenic strains to cells of nonsecretors [12]. The larger population of bacteria might multiply in the absence of specific immune protection and induce a strong inflammatory response.…”
Section: The Immune Responses Of Secretors and Nonsecretors To Urinarmentioning
confidence: 99%
“…Bacterial adherence to epithelial cells depends on receptor expression by the host (11,25). Patients with cystic fibrosis were recently shown to have a higher density of receptors for P aeruginosa on their respiratory tract epithelial cells than controls (24).…”
Section: Methodsmentioning
confidence: 99%